Astemizole as a drug to inhibit the effect of SARS-COV-2 in vitro. (July 2021) - Wang, Xiangjun; Lu, Jiayu; Ge, Shuai; Hou, Yajing; Hu, Tian; Lv, Yuexin; Wang, Cheng; He, Huaizhen
Abstract: Since the beginning of December 2019, a novel Coronavirus severe respiratory disease, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) which also been termed 2019-new CoV (2019-nCoV), has continued to spread worldwide. As of August 27, 2020, a total of 24, 232, 429 people have been infected and 826, 518 people have died. In our study, we found that astemizole can antagonize ACE2 and inhibit the entry of SARS-COV-2 spike pseudovirus into ACE2-expressed HEK293T cells (ACE2hi cells). We analysied the binding character of astemizole to ACE2 by molecular docking and surface plasmon resonance (SPR) assays and molecule docking, SARS-COV-2 spike pseudotype virus was also taken to investigate the suppression viropexis effect of astemizole. The results showed that astemizole can bind to the ACE2 receptor and inhibit the invasion of SARS-COV-2 Spike pseudoviruses. Thus astemizole represent potential drug candidates that can be re-used in anti-coronavirus therapies. Graphical abstract: Image 1 Highlights: Astemizole can significantly reduce COVID-19 Spike pseudotype virus into ACE2 cells, may be a potential drug for the treatment of COVID-19 pneumonia. Astemizole can bind to the ACE2 receptor through SPR analysis. The computer virtual docking technology infers that the astemizole forms a hydrogen bond with the ACE2 protein.